Aplikasi Sistem Pembayaran Klinik Akupuntur Sehat Sejahtera Menggunakan Metode RAD - Astuti, Puji; Yusnaeni, Wina (Jurnal Informatika Universitas Pamulang, 2021)
Alternative medicine has long been known among the public as a treatment that can cure a variety of diseases. Types of alternative medicine are many types of one that we know in the form of acupuncture treatment. Acupuncture treatment in Indonesia is not new and there are many people who do treatment in this way , even it has been fairly official because it is already a clinic - clinics scattered throughout Indonesia. One of the acupuncture clinics located at Jl. Lelel 5 Pamulang Timur, South Tangerang. At Klinik Akupuntur Sehat Sejahtera offers a variety of acupuncture packages, only in the system used in this clinic is still manual ranging from recording patient data, drug data to payment transactions. With that reason, a solution is needed that can be used to facilitate data collection and also more efficient in data storage, namely with desktop application information system. By using rad research method as the flow of the system. The results obtained from RAD methods and applications with JAVA can help admins in inputting patient data, drug data and payment transactions at healthy acupuncture clinics in east Pamulang.